The Implementation of Health Protocols by The Elderly in Urban and Rural Area in East Java, Indonesia - Sofia Rhosma Dewi; Bima Warsita Adi; Wulan Purbowati; Intania Intania (Universitas Muhammadiyah Jember, 2022)
The COVID-19 pandemic has occurred since 2020 and since the appearance of the first case, Indonesia has experienced three peaks of COVID-19 attacks. The elderly are one of the vulnerable groups with high mortality due to comorbidities. Implementation of health protocols is the key to controlling the incidence of COVID-19. The purpose of this study was to analyze the differences in the implementation of health protocols for the elderly living in urban and rural areas. This is a correlational study with a cross-sectional approach. This study involved 447 elderly living in urban and rural areas who were taken by purposive sampling technique. The data was taken using a questionnaire instrument and the analysis was carried out using the Mann Whitney test using SPSS 21 for windows. The results showed that of the 235 elderly living in urban areas, 52.3% of respondents showed compliance with health protocols and of 212 respondents who lived in rural areas, only 15% of elderly people complied with health protocols. The results by Mann Whitney analysis showed p-value of 0.000 smaller than α 0.05 so it was concluded that there was a difference in compliance to the implementation of health protocols between the elderly in rural and urban areas. People in rural areas, especially the elderly, still do not believe in COVID-19. So it is necessary to do health education with an approach that is in line with their value, for example, with a cultural approach.